PERAN ORANGTUA DALAM MENANAMKAN KEMANDIRIAN PADA ANAK USIA DINI DI RA AT-TAUHIDIYAH SERANG - Ahmad Mubarok (LPPM Universitas Bina Bangsa, 2024)
This research is motivated by the high level of independence in children, which is thought to be related to the formation of independence in children. The aim of this research is to describe the development of children's independence in families at RA At-Tauhidiyah, Serang City by instilling self-confidence in children, developing children's habits and developing communication with children. This research is quantitative descriptive. The population and sample of this study were parents of children aged 5-6 years. The data collection technique is a questionnaire and data collection, the tools used are a questionnaire and data analysis techniques through percentage calculations. The results of the research show that increasing independence through increasing parental self-confidence is classified as good, increasing independence through parental socialization is classified as very good, and increasing parental independence is classified as very good. Good communication between parents and children is considered very good. These three aspects of research greatly influence children's independence